The Satisfaction Analysis of Local Public Transportation (Carry) Services at Batam, Indonesia - Jeffrey Victory; Andri Irfan Rifai; Susanty Handayani (International Journal Labs, 2022)
Carry is one of the public transportation found in Batam, Indonesia. However, there is a need for innovation so that this public transportation can compete with other public transportation and private vehicles. Therefore, this study was carried out to determine what variables must be considered when determining the level of public satisfaction with